2017
DOI: 10.1038/nmicrobiol.2017.1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of envelope permeability and antibiotic influx and efflux in Gram-negative bacteria

Abstract: International audienceResearchers, clinicians and governments all recognize antimicrobial resistance as a serious and growing threat worldwide. New antimicrobials are urgently needed, especially for infections caused by Gram-negative bacteria, whose cell envelopes are char- acterized by low permeability and often contain drug e ux systems. Individual bacteria and populations control their internal concentrations of antibiotics by regulating proteins involved in membrane permeability, such as porins or e ux pum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
285
3
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 254 publications
(299 citation statements)
references
References 84 publications
4
285
3
7
Order By: Relevance
“…This is key information necessary to approach the “Structure Intracellular Concentration Activity relationship” (SICAR), a new concept for the future antibiotic candidate that will correlate permeation parameters to activity properties for a defined molecule 41 . The key role of outer membrane permeability in the accumulation of cephalosporin molecules, and by extension of those of the ß-lactam family, in the periplasmic space can be now quantified.…”
Section: Discussionmentioning
confidence: 99%
“…This is key information necessary to approach the “Structure Intracellular Concentration Activity relationship” (SICAR), a new concept for the future antibiotic candidate that will correlate permeation parameters to activity properties for a defined molecule 41 . The key role of outer membrane permeability in the accumulation of cephalosporin molecules, and by extension of those of the ß-lactam family, in the periplasmic space can be now quantified.…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing a set of 147 compounds (either approved human drugs or late‐stage compounds), O'Shea and Moser reported that effective compounds against Gram‐negative pathogens (i) were more polar than other classes of drugs, as shown by their clog D 7.4 values (predicted octanol/water distribution coefficient at pH = 7.4) and (ii) had a molecular weight (MW) lower than 600 Da . These properties are consistent with the sophisticated architecture of bacterial membranes . The authors suggested that research into new ATBs should focus on relatively small and polar molecules .…”
Section: Introductionmentioning
confidence: 92%
“…One of the key problems facing us since the modern discovery of antibiotics is our limited understanding of the physicochemical properties of ATBs, which is necessary to ensure successful micro‐organism penetration and accumulation . For example, the Gram‐negative bacterium envelope consists of an OM and an inner membrane (IM), separated by a periplasmic space . The OM is a very effective barrier for amphipathic compounds, whereas the IM impedes penetration of hydrophilic molecules .…”
Section: Introductionmentioning
confidence: 99%
“…The Gram-negative envelope comprises an inner membrane (IM), which is a symmetric phospholipid bilayer; a thin peptidoglycan (PG) layer ensuring the cell shape; and an outer membrane (OM) that is an asymmetric bilayer, composed of an inner leaflet of phospholipids and an outer leaflet of lipopolysaccharide (LPS) [8]. The OM is a barrier to both hydrophobic and hydrophilic compounds, including necessary nutrients, metabolic substrates and antimicrobials, but access is provided by the water filled b-barrel channels called porins [6,[9][10][11][12]. In Escherichia coli, the channels of the general porins OmpF and OmpC are size restricted and show a preference for passage of hydrophilic charged compounds, including antibiotics such as b-lactams and fluoroquinolones.…”
Section: Introductionmentioning
confidence: 99%
“…These porins are conserved throughout the phylum of g-proteobacteria [13]. Additionally, tripartite RND (Resistance-Nodulation-cell Division) efflux pumps, such as AcrAB-TolC in E. coli, play a major role in removing antibiotics from the periplasm [7,12]. Not surprisingly, MDR clinical isolates of Enterobacteriaceae generally exhibit porin loss and/or increased efflux, which act in synergy to reduce the intracellular accumulation of antibiotics below the threshold that would be efficient for activity [10].…”
Section: Introductionmentioning
confidence: 99%